First record of the genus Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from China, with description of a new species - Deng, Min; Xing, Jichun (Zootaxa, 2024)
The soft scale insect genus Marsipococcus Cockerell & Bueker, 1930 (Hemiptera: Coccomorpha: Coccidae) is reported for the first time from China; a new species, Marsipococcus brideliae sp. n., is described and illustrated from Guizhou Province on Bridelia retusa (Phyllanthaceae). A key is given to distinguish all four species in the genus. Type specimens of the new species are deposited at the Institute of Entomology, Guizhou University, Guiyang, China and the collection at the Department of Forestry Protection, Beijing Forestry University, Beijing.